2019
DOI: 10.3390/e21111028
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Transitions in a One-Dimensional Katz–Lebowitz–Spohn Model

Abstract: Dynamical transitions, already found in the high-and low-density phases of the Totally Asymmetric Simple Exclusion Process and a couple of its generalizations, are singularities in the rate of relaxation towards the Non-Equilibrium Stationary State (NESS), which do not correspond to any transition in the NESS itself. We investigate dynamical transitions in the one-dimensional Katz-Lebowitz-Spohn model, a further generalization of the Totally Asymmetric Simple Exclusion Process where the hopping rate depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Regarding methods, based on the agreement between MF and KMC found in [10] and in our work, it would be interesting to rigorously assess whether, and to what extent, MF results can become exact in the thermodynamic limit. It would also be worth investigating the relaxation towards the stationary state, in which dynamical transitions without a static counterpart have been found in (T)ASEP with OBCs [18][19][20], also (at least with approximate methods) in the presence of Langmuir kinetics [21,22] or additional interactions between particles [23,24]. Finally, we hope that these theoretical results can stimulate progress in the experimental studies, which as far as we know have been so far limited to resetting in single-particle systems [25,26].…”
Section: -P2mentioning
confidence: 99%
“…Regarding methods, based on the agreement between MF and KMC found in [10] and in our work, it would be interesting to rigorously assess whether, and to what extent, MF results can become exact in the thermodynamic limit. It would also be worth investigating the relaxation towards the stationary state, in which dynamical transitions without a static counterpart have been found in (T)ASEP with OBCs [18][19][20], also (at least with approximate methods) in the presence of Langmuir kinetics [21,22] or additional interactions between particles [23,24]. Finally, we hope that these theoretical results can stimulate progress in the experimental studies, which as far as we know have been so far limited to resetting in single-particle systems [25,26].…”
Section: -P2mentioning
confidence: 99%
“…We summarize all the analytical results in a dynamical phase diagram (figure 5), partitioning the HD phase into regions (subphases), whose border lines coincide with the singularities described above. We first distinguish two main subphases, denoted as HD-s ("slow") and HD-f ("fast"), which respectively correspond to the regions where λ min (∞) depends on α or not (the terms "slow" and "fast" to denote these subphases have been previously used in [19,21]). In particular, in the fast phase λ min (∞) is not only independent of α but it also takes the highest admissible value at given β, namely…”
Section: Analytical Resultsmentioning
confidence: 99%
“…In the first place, we have observed that, depending on the model parameters, the singularity associated with the dynamical transition may also appear as a discontinuity in the first derivative of the relaxation rate with respect to either the injection or extraction rate. This is a novel feature, since both in the pure TASEP (which is exactly solvable) [16,17,18] and in some variants (including the TASEP with balanced Langmuir kinetics) [19,20,21] the relaxation rate only exhibits discontinuities in the second derivative (in such cases we speak of second-order-like dynamical transitions). Furthermore, we have found that, when the relaxation rate exhibits first-order singularities, the whole spectrum of the mean-field relaxation matrix exhibits a non-trivial behaviour, being characterized (at finite size) by avoided crossings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding methods, based on the agreement between MF and KMC found in [10] and in our work, it would be interesting to rigorously assess whether, and to what extent, MF results can become exact in the thermodynamic limit. It would also be worth investigating the relaxation towards the stationary state, in which dynamical transitions without a static counterpart have been found in (T)ASEP with OBCs [18][19][20], also (at least with approximate methods) in the presence of Langmuir kinetics [21,22] or additional interactions between particles [23,24]. Finally, we hope that these theoretical results can stimulate progress in the experimental studies, which as far as we know have been so far limited to resetting in single-particle systems [25,26].…”
mentioning
confidence: 99%